Higher Education and Economic Transition in Guyana: Preparing a Future-Ready Workforce for Emerging Industries - Paul (Sr.), Stanley Anthony Vivion; Joseph, Justin; Paul (Jr.), Stanley Anthony Vivion; McDonald, Coretta; Solomon, Orande Kenneatior; Rambhajan, Shenelle (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Guyana is undergoing one of the most significant economic transformations in its modern history, driven by rapid expansion in energy, infrastructure, logistics, digital services, and related industries. This transition necessitates a higher-education sector capable of producing a skilled, future-ready workforce aligned with national development priorities. This article examines the evolving relationship between higher education and Guyana’s economic transformation, identifying critical gaps in workforce readiness, curriculum relevance, institutional capacity, and stakeholder coordination. Drawing on economic-development literature, global human-capital frameworks, and regional analyses, the article proposes strategic imperatives for building an agile, innovation-driven higher-education system. The discussion underscores the importance of curriculum modernization, industry-university collaboration, lifelong learning pathways, digital and technical competencies, and governance reform. Recommendations highlight how Guyana can leverage higher education as a catalyst for inclusive, sustainable growth.